2011
DOI: 10.1007/s15010-011-0101-0
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver agreement on signs and symptoms of patients with acute febrile illness

Abstract: High agreement was observed for most of the clinical data assessed, and symptom grading was feasible. Some physical findings were rare and their inclusion in a structured form may not be justified in this setting. The questionnaire application showed good reliability for the most frequent signs and symptoms and may prove to be useful at gathering data for surveillance and research at sentinel sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 17 publications
1
9
1
Order By: Relevance
“…All were trained to perform and record standardized clinical evaluations and fill a form containing 28 symptoms and 25 signs potentially useful in the differential diagnosis of febrile illnesses, according to literature review and specialists consensus. Interobserver agreement on signs and symptoms was evaluated in a subsample of 140 patients and was almost perfect (kappa > 0.80) for most collected clinical data [24]. The questionnaire is available online for consultation and details on its development have been described elsewhere [24].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All were trained to perform and record standardized clinical evaluations and fill a form containing 28 symptoms and 25 signs potentially useful in the differential diagnosis of febrile illnesses, according to literature review and specialists consensus. Interobserver agreement on signs and symptoms was evaluated in a subsample of 140 patients and was almost perfect (kappa > 0.80) for most collected clinical data [24]. The questionnaire is available online for consultation and details on its development have been described elsewhere [24].…”
Section: Methodsmentioning
confidence: 99%
“…Interobserver agreement on signs and symptoms was evaluated in a subsample of 140 patients and was almost perfect (kappa > 0.80) for most collected clinical data [24]. The questionnaire is available online for consultation and details on its development have been described elsewhere [24]. …”
Section: Methodsmentioning
confidence: 99%
“…We used a summarised version of a previously validated semi‐structured sign and symptom standardised questionnaire for AFI (Daumas et al, 2011). The research team received extensive training based on the instrument procedure manual and was instructed on question formulation and tabulation methods used in the tool (available online as a supplementary material of Daumas et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…However, they have rarely been used for dengue. Daumas et al (2011) validated a semi‐structured questionnaire and its procedure manual, standardising a clinical approach to AFI, including dengue. These authors found substantial agreement for most of the signs and symptoms, suggesting that the standardised instrument could be helpful in evaluating AFI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation